Development and validation of a questionnaire to measure the congenital heart disease of children’s family stressor - Zhang, Yi; Zhou, Hang; Bai, Yangjuan; Chen, Zhisong; Wang, Yanjiao; Hu, Qiulan; Yang, Mingfang; Wei, Wei; Ding, Lan; Ma, Fang (Frontiers in Public Health, 2024)
Background: Families of children with congenital heart disease(CHD) face tremendous stressors in the process of coping with the disease, which threatens the health of families of children with CHD. Studies have shown that nursing interventions focusing on family stress management can improve parents' ability to cope with illness and promote family health. At present, there is no measuring tool for family stressors of CHD.The items of scale were generated through qualitative interviews and literature review. Initial items were evaluated by 7 experts to determine content validity.Factor analysis and reliability testing were conducted with a convenience sample of 670 family members. The criterion-related validity of scale was calculated using scores on the Self-Rating Anxiety Scale (SAS).The CHD Children's Family Stressor Scale consisted of 6 dimensions and 41 items. In the exploratory factor analysis, the cumulative explained variance of the six factors was 61.085%. In the confirmatory factor analysis, the 6 factors in the exploratory factor analysis were well validated, indicating that the model fits well. The correlation coefficient between CHD Children's Family Stressor Scale and SAS was r=0.504(P<0.001), which indicated that the criterion-related validity of scale was good.In the reliability test, Cronbach's α coefficients of 6 sub-scale of were 0.774 to 0.940, the scale-level Cronbach's α coefficient value was 0.945.The study indicates that the CHD Children's Family Stressor Scale is valid and reliable, it is recommended for use in clinical practice to assess the CHD children's family stressor.